2019
DOI: 10.1016/j.jsxm.2019.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Non-Natural Death Associated with Sexual Activity: Results of a 25-Year Medicolegal Postmortem Study

Abstract: Introduction Non-natural deaths associated with sexual activity may occur either with or without the involvement of other persons. Aim The present study provides an overview of cases of non-natural death related to sexual activities as well as recommendations of how to handle these cases and to identify potentially dangerous pleasure-enhancing techniques. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…These results show that fatalities correlate with the usage of alcohol and drugs. The numbers correspond with the results from Bunzel et al for autoerotic fatalities [8].…”
Section: Toxicologysupporting
confidence: 82%
See 2 more Smart Citations
“…These results show that fatalities correlate with the usage of alcohol and drugs. The numbers correspond with the results from Bunzel et al for autoerotic fatalities [8].…”
Section: Toxicologysupporting
confidence: 82%
“…A 25-year medicolegal postmortem study from 1993 to 2017 on 16,437 autopsies was conducted in Germany. Of the 74 cases of non-natural death associated with sexual activity, 3 cases (4.05%) were associated with BDSM activities [ 8 ]. The 17 cases are described in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of massive dopamine release in hypoxia followed by resumption of tonic levels drew our attention to a little discussed clinical and forensic problem, namely autoerotic asphyxiation (AEA) behaviors (Quinn and Twomey, 1998;Bunzel et al, 2019). Increase in striatal and nucleus accumbens dopamine transmission has been shown during sexual activity (Pfaus et al, 1990(Pfaus et al, , 1995.…”
Section: Dopamine Increases Reversibly During a Brief Episode Of Hypoxiamentioning
confidence: 99%
“…There are a few empirical studies of injury rates related to specific consensual BDSM practices, including medical case reports that are clearly linked to BDSM activities. Bunzel and colleagues 30 examined 16,437 medicolegal autopsies performed between 1993 and 2017 at the Institute of Legal Medicine at University Hospital, Goethe University in Frankfurt, Germany. Researchers found that 3 deaths were related to partnered consensual BDSM activities.…”
Section: Injury Rates For Bdsm Activitiesmentioning
confidence: 99%